The changes in bladder function and symptoms after robot-assisted sacrocolpopexy and transvaginal mesh surgery for pelvic organ prolapse - Chia-Hua Chang; Tsung-Hsien Su; Hui-Hsuan Lau (Elsevier, 2024)
Objective: This study is aimed to compare the impact on bladder function and symptoms between robotic sacrocolpopexy (RSC) and transvaginal mesh surgery (TVM) in women with pelvic organ prolapse. Materials and methods: This prospective controlled study enrolled patients who received RSC or TVM at our hospital between March 2020 and June 2022. We compared preoperative and postoperative bladder function between two groups by using a questionnaire of lower urinary tract symptom (LUTs) for subjective assessment and urodynamic study for objective assessment. Results: A total of 60 patients were enrolled, of whom 30 received RSC and 30 received TVM. In LUTs analysis, the RSC group had a higher risk of de novo stress urinary incontinence than the TVM group (33.3% vs. 3.3%, p = .007). Urodynamic studies showed that both groups had a deterioration in maximal urethral closure pressure postoperatively (RSC: 56.9 ± 17.1 vs. 44.2 ± 15.5 cmH2O; and TVM: 61.2 ± 29.4 vs. 47.6 ± 19.7 cmH2O, p < .01 and p = .03, respectively). The incidence of urodynamic stress incontinence was also significantly increased after RSC (33.3% vs. 76.7%, p = .01). The de novo urodynamic stress incontinence rate was 46.7% after RSC, which was not significantly different to the TVM group (26.7%, p = .16). In the TVM group, the incidence of voiding difficulty decreased after surgery (43.3% vs. 10.0%, p < .01), and urodynamic measurements revealed that the prevalence of urine retention decreased (43.3% vs. 16.7%, p < .01). In the RSC group, the incidence of incomplete emptying sensation decreased (36.7% vs. 13.3%, p = .04), and urodynamic measurements showed that none of the patients had bladder outlet obstruction, underactive detrusor, or urine retention after surgery. Conclusion: RSC and TVM are both beneficial to improve voiding function in women with pelvic organ prolapse. However, a deterioration in urethral function was observed and the de novo SUI rate was higher in the RSC group than in the TVM group.